Erratum to "Digital wayfinding systems in hospitals: A qualitative evaluation based on managerial perceptions and considerations before and after implementation" [Appl. Ergon. 90 (2020) 103260]. (September 2021) - Morag, Ido; Pintelon, Liliane
Abstract: Despite the benefits that digital wayfinding systems offer hospital visitors and patients as well as the hospitals themselves, their actual presence in hospitals is low. This study, carried out in twenty hospitals, presents an evaluation of these systems. Interviews with hospital managers (with and without systems) indicate considerations and evidence-based information that are new to the literature such as reducing task complexity and overall user stress and anxiety; enhancing user control and empowerment; decreasing the amount of time medical staff must devote to providing directions to patients; and reducing rate of delayed and missed appointments. While these systems have considerable potential for assisting the elderly and those with disabilities, this potential is not being realized. Findings may benefit system planners, hospital administrators and eventually provide users with more suitable systems upon which to rely.